2013
DOI: 10.3390/md11010165
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Determination of Two Novel Phlorotannins from the Brown Alga Ecklonia kurome Okamura, and Their Radical Scavenging Activities

Abstract: Two novel phlorotannins with a molecular weight of 974, temporarily named 974-A and 974-B, were isolated from the polyphenol powder prepared from the edible marine brown alga Ecklonia kurome Okamura, and their chemical structures were determined by spectroscopic method. The isolated yield of the total of 974-A and 974-B was approximately 4% (w/w) from the polyphenol powder. In 974-A, the carbon at the C2′ position in the A ring of phlorofucofuroeckol-A forms a C–C bond with the carbon at the C2″ position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Phlorotannins purified from others brown algae such as Ecklonia sp. has shown cytocompatible effects to human fetal lung fibroblasts cell line (MRC-5) [28] and macrophage-like form cell (THP-1 cell) [15]. A recent report using dieckol, an isolated compound from Ecklonia stolonifera Okamura algae extracts, also presented more selective effects to Hek-293 compared to a tumor cell line Hep3B [29].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Phlorotannins purified from others brown algae such as Ecklonia sp. has shown cytocompatible effects to human fetal lung fibroblasts cell line (MRC-5) [28] and macrophage-like form cell (THP-1 cell) [15]. A recent report using dieckol, an isolated compound from Ecklonia stolonifera Okamura algae extracts, also presented more selective effects to Hek-293 compared to a tumor cell line Hep3B [29].…”
Section: Discussionmentioning
confidence: 97%
“…Cytotoxic studies using total extract obtained from a variety of algae have demonstrated that brown algae are a potential source of compounds presenting biological activities on tumor cells [15] 50 showed greater IC 50 (>1000 μg/mL) [25]. A study with red algae Gracilaria tenuistipitata C.F.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, YotsuYamashita M and his partner isolated and determined two novel phlorotannins 974-A (9) and 974-B (10) from E. kurome with radical scavenging activities (shown in Fig. 86.3) [7].…”
Section: Phlorotanninsmentioning
confidence: 99%
“…Infra red (IR) spectra were measured on a Perkin-Elmer (Wellesley, MA) spectrophotometer. Each compound was identified by comparison with previously published spectral data Yotsu-Yamashita et al, 2013).…”
Section: Identification Of Phlorotanninsmentioning
confidence: 99%